PEMBERDAYAAN MASYARAKAT MELALUI KEGIATAN IPTEK BAGI MASYARAKAT (IbM) KELOMPOK PEMBUDIDAYA IKAN LELE DAN PEMBUATAN DIVERSIFIKASI PRODUK OLAHANNYA DI KABUPATEN KARANGANYAR - Dian Rachmawati Afandi, Emi Widiyanti, Bekti Wahyu Utami, (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
Character catfish farming is relatively easy to implement by thepublic, this is the underlying reason why catfish farming is also widelyhailed by the public in such Karanganyar by Ulam Nastiti groups and NgudiMulyo groups located in the Suruh Village Tasikmadu Sub District KaranganyarDistrict. Some of the activities and the introduction of appropriatetechnology is given to the farmers in order to make the group more empowered.So far, almost all activities are conducted though the implementationis not fully compliant proposal, but the team's dedication consideration isthat these activities should be based on partner needs/goals. So althoughexcavation needs on time preparation of proposals have been made, but ifthe reality field conditions change then certainly needs changing partners,too, so that any given solution must be adjusted.Keywords : empowerment, catfish farming, and processed fish